Pengurusan Reka Bentuk Hiasan Dalaman Dan Lanskap Pada Kediaman Dengan Menggunakan Feng Shui di Taman Kemboja 4a, Bukit Sentosa - Norhayati, Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study describes the concepts and methods of Feng Shui for interior design and residential landscapes. A study conducted in Taman Kemboja 4A, Bukit Sentosa, Selangor is also to analyze the reception area residents to use in the management of Feng Shui for interior design and residential landscapes. Next, through the analysis of qualitative and quantitative methods, researchers have made a research on the concepts, methods and acceptance residents in the management of Feng Shui study on landscape design and decoration of their homes. The findings found that a handful of people understand and know the park concept and the method of Feng Shui. However, residents of the area do not agree to use Feng Shui to the management of landscape and interior design of their homes. This is evidenced by the findings that only 19% of respondents from Taman Kemboja 4A agreed to use Feng Shui to the management of the design of residential interiors and landscapes.